Determination of Trace Element Contents of Some Spice Samples by Using FAAS - Kiliçel, Fevzi; Karapinar, Hacer Sibel (Asian Journal of Chemistry, 2018)
This study purposed to analyze the concentrations of 10 trace elements in aromatic spices (cinnamon, cumin, ginger, black pepper, red pepper and powdered pepper) by flame atomic absorption spectrometry (FAAS), after wet burning method. The analytical method was validated by linearity, detection limits, accuracy and recovery experiments values in all cases. The concentration of trace elements were measured in the range of 17.13–28.62, 3.09–8.57, 122.9–482.0, 492–999 and 28490–69630 mg kg-1 in order of zinc, copper, manganese, magnesium and calcium ions. As the toxic elemental contents were measured in the range of 1.61–14.06, 16.83–23.43, 27.03–56.07, 6.15–15.79 and 702–991 mg kg-1 in order of cobalt, lead, nickel, chromium and iron. The results were compared with the literature values. Pb, Ni, Fe and Cr elements are above the permissible limits and other elements are found to be at standard levels.